1985
DOI: 10.1159/000153585
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Genetic Load with Changing Socio-Cultural Environment

Abstract: Variability in genetic load has been studied against their contrasting socio-economic and cultural backgrounds in two endogamous populations, namely, the well-off Brahmins and the low income Jalaris of Visakhapatnam, India. The A (genetic and environmental damage) and B (hidden genetic damage) estimates are higher in Jalaris. Decreased A estimates indicate the better medical care in Brahmins; the value of B could be low since many of the deaths in consanguineous families due to infectious diseases are now rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In fact, the recently reported high inbreeding coefficient (0.0225) of the Iraqi population puts Iraq among the highest in the world except perhaps for strongly isolated socie ties with a high genetic load [Indira et al, 1976;Inbaraj, 1979, 1980;Srikumari et al, 1985], Hamamy et al [1986] have calculated the Iraqi inbreeding coef ficient from their data of 29.2% first-cou- sins marriages, 10.1% first cousins once removed marriages, 17.1 % second-cousins marriages and 11.4% of marriages be tween beyond second cousins among a to tal of 4,491 marriages.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the recently reported high inbreeding coefficient (0.0225) of the Iraqi population puts Iraq among the highest in the world except perhaps for strongly isolated socie ties with a high genetic load [Indira et al, 1976;Inbaraj, 1979, 1980;Srikumari et al, 1985], Hamamy et al [1986] have calculated the Iraqi inbreeding coef ficient from their data of 29.2% first-cou- sins marriages, 10.1% first cousins once removed marriages, 17.1 % second-cousins marriages and 11.4% of marriages be tween beyond second cousins among a to tal of 4,491 marriages.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies conducted on effects of inbreeding in different populations revealed elevated levels [29,10,11,16,27,28,14,1,23] of prereproductive mortality among the offspring of consanguineous marriages. But, most of the studies conducted in India [18,20,21,13,9,2,3,32,22] did not reveal any significant effect of inbreeding on mortality. Lack of inbreeding effects in these populations support the Sanghvi's [25,26] contention that in areas where the current levels of inbreeding are high and where inbreeding has been the custom for over two milliennia or perhaps longer, the effects of inbreeding may not be perceptible.…”
Section: Introductionmentioning
confidence: 99%